An evaluation of the childhood family structure measures from the sixth wave of the British Household Panel Survey - Marco Francesconi (University of Essex, Institute for Social and Economic Research (ISER), 2002)
This paper performs an evaluation of the data collected in the sixth wave of the BHPS on childhood family structure. After comparing such data with a large number of studies using external sources, we find that the BHPS overestimates the proportion of people who report an experience of life in a non-intact family during childhood by about 12%. Although an explanation based on recall error that deteriorates with the age of the BHPS informants is possible, this overestimation is likely to be accounted for by non-ignorable attrition that may affect most of the comparison studies using longitudinal data. Conversely, comparisons with other independent measurements from the BHPS itself reveal that the wave-6 data underestimate the proportion of young people having experienced part of their childhood in a non-intact family by about 8%. The probability of disagreement between these two statistics is strongly associated with poor interview characteristics, which may affect the comparison measure more than the wave-6 measure. In general, however, despite such differences, there is a substantial degree of similarity between the family structure information collected in the sixth wave of the BHPS and the host of highly diverse records against which it has been compared.
Keywords: 330